Sprint exercise performance: Does metabolic power matter? - Bundle, M. W.; Weyand, P. G. (Exercise and Sport Sciences Reviews, 2012)
Prevailing physiological paradigms explain both sprint and endurance exercise performance in terms of the availability of metabolic energy. However, for all-out efforts of 60 s or less, the prevailing view is no longer viable. Contemporary evidence indicates that sprinting performance is determined by musculoskeletal force application, with a duration dependency explained by the intrinsically rapid rates at which skeletal muscle fatigues in vivo.